Generation of High-Titer Defective HSV-1 Vectors Using an IE 2 Deletion Mutant and Quantitative Study of Expression in Cultured Cortical Cells. (March 1996) - Lim, F.; Hartley, D.; Starr, P.; Lang, P.; Song, S.; Yu, L.; Wang, Y.; Geller, A.I.
Vectors based on herpes simplex virus type 1 (HSV-1) show promise for gene transfer into mammalian cells because of their wide host range, efficient infection and ability to deliver genes to nondividing cells. Defective HSV-1 vectors, or amplicons, are plasmid vectors which are unable to propagate on their own but contain specific HSV-1 sequences that, in the presence of helper virus, support DNA replication and subsequent packaging into virus particles. We compared three replication-incompetent HSV-1 mutants (KOS strain 5 dl l.2, strain 17 D30EBA, KOS strain dl20) as the helper virus for packaging the prototype defective HSV-1 vector, pHSVlac, which uses the HSV-1 immediate-early (IE) 4/5 promoter to regulate expression of the Escherichia coli lacZ gene. Use of 5 dl 1.2, which contains a deletion in the IE 2 gene, consistently produced virus stocks that contained a high level of vector, undetectable levels of wild-type HSV-1 and a ratio of vector to helper greater than 1. Virus stocks prepared using 5 dl 1.2 were superior to those prepared using helper viruses that harbor a deletion in the IE 3 gene, either D30EBA or dl20, and supported more efficient gene transfer than possible with previously published procedures. Lactate dehydrogenase efflux assays in rat cortical cultures showed that 5 dl 1.2 was no more cytotoxic than either D30EBA or dl20, despite the expression of more viral genes. Rat cortical cultures infected with pHSVlac packaged with either 5 dl 1.2 or D30EBA were used to quantify the stability of vector expression. Our results show a decrease in the number of cells with detectable levels of β-galactosidase to 30% of peak levels after one week, irrespective of the helper virus used. However, simultaneous superinfection with 5 dl 1.2, but not with either D30EBA or dl20, produced a transient increase in the number of cells expressing β-galactosidase. Superinfection with 5 dl 1.2 at 9 days after gene transfer increased the number of cells expressing detectable β-galactosidase back topeak levels, most probably because of reactivation of the IE 4/5 promoter in pHSVlac. These results thus provide the first quantitative demonstration of long-term persistence of defective HSV-1 vectors in neurons.